Diagnosa Penyakit Osteoporosis Menggunakan Metode Certainty Factor - Yuhandri Yuhandri (Ikatan Ahli Informatika Indonesia (IAII), 2018)
The purpose of this research is to build an Expert System application for the diagnosis of Osteoporosis disease. This study uses Certainty Factor method because in this method there is a value of the value of trust (Measure Of Belief) and the value of distrust (Measure Of Disableief) on a symptom, where later the value can produce the value of CF (Certainty Factor) as a benchmark, the greater the value of CF (Certainty Factor) obtained the greater the chance that the disease will attack us, where the results are displayed in terms of user conditions associated with Osteoporosis. The results of this study also comes with disease and treatment solutions are displayed in the form of websites using PHP programming and is also useful to perform early diagnosis of a disease that is perceived by the userthus helping the user in recognizing the symptoms of Osteoporosis disease they feel, as well as with the existence of this expert system can be used as an alternative solution for the community to make early diagnosis of the symptoms of Osteoporosis disease they feel before doing direct consultation with experts in this case specialist bone. This system is able to store expert knowledge representation based on certainty factor with accuracy of 80%.